A comparative analysis of immunogenicity and safety of an enterovirus 71 vaccine between children aged 3-5 years and infants aged 6-35 months - Wei Gu; Gang Zeng; Yue-mei Hu; Yuan-Sheng Hu; Ying Zhang; Ya-ling Hu; Yang Wang; Jing-Xin Li; Feng-Cai Zhu (Taylor & Francis Group, 2018)
Background: The Sinovac enterovirus 71 (EV71) vaccine has shown good safety, immunogenicity, and efficacy in infants aged 6-35 months, whom are considered as the priority of the target population. However, 3-5 years old children accounted for approximately 30% of HFMD cases and are also worth our attention. Methods: A randomized, double-blind, placebo-controlled, batch-to-batch consistency clinical trial enrolling 1400 participants aged 6-59 months was performed. We pooled the participants receiving three batches of EV71 vaccine together and then stratified them into the 6-35 months and 3-5 years. The non-inferiority analysis of the geometric mean titer (GMT) of EV71 neutralizing antibody post-vaccination was the primary endpoint. Results: In the vaccine group, the GMT of 242 children aged 3-5 years was 132.72 (95% CI, 110.3-159.6), which was non-inferior to that generated in 717 infants aged 6-35 months. Following the vaccination, the incidence of adverse reactions was less frequent in children aged 3-5 years (47.0%) than that found in infants aged 6-35 months (60.1%) (p = 0.0026). Conclusions: Our study indicated that the EV71 vaccine was also safe in children aged 3-5 years, with non-inferior immunogenicity to that in infants aged 6-35 months.